Continuous Dissolved Gas Tracing of Fracture‐Matrix Exchanges. Issue 17 (7th September 2020) - Hoffmann, R.; Goderniaux, P.; Jamin, P.; Chatton, E.; de la Bernardie, J.; Labasque, T.; Le Borgne, T.; Dassargues, A.
Abstract: Transport in fractured media plays an important role in a range of processes, from rock weathering and microbial processes to contaminant transport, and energy extraction and storage. Diffusive transfer between the fracture fluid and the rock matrix is often a key element in these applications. But the multiscale heterogeneity of fractures renders the field assessment of these processes extremely challenging. This study explores the use of dissolved gases as tracers of fracture‐matrix interactions, which can be measured continuously and highly accurately using mobile mass spectrometers. Since their diffusion coefficients vary significantly, multiple gases are used to probe different scales of fracture‐matrix exchanges. Tracer tests with helium, xenon, and argon were performed in a fractured chalk aquifer, and resulting tracer breakthrough curves are modeled. Results show that continuous dissolved gas tracing with multiple tracers provides key constrains on fracture‐matrix interactions and reveal unexpected scale effects in fracture‐matrix exchange rates. Plain Language Summary: Fractures provide pathways to flow, chemical elements and energy, as well as habitats for microorganisms in the Earth's subsurface. Due to diffusion and reaction, dissolved chemical elements are continuously exchanged between groundwater flowing in the fractures and the surrounding rock matrix. This process exerts a strong influence on many biogeochemical processes. Yet, due to multiscale heterogeneity of fracture systems, the characterization of fracture‐matrix interactions is challenging and there is high uncertainty on relevant conceptual models. This study explores the use of dissolved gases as tracers of fracture‐matrix interactions. Their larger diffusion coefficients compared to classical tracers allow a deeper penetration into the matrix compared to conventional fluorescent dyes, and recent field mass spectrometers allow a continuous and highly accurate monitoring. Field tracer test results are interpreted with mathematical models, providing new constraints on the definition and parametrization of transport models in fractured rocks. Key Points: Multitracer tests were performed in a fractured chalk aquifer using continuously monitored solute and dissolved gas tracers The different molecular diffusion coefficients of dissolved gas tracers provide new information on fracture‐matrix exchanges A methodology is presented to invert peak time, peak intensity, and tailing slope to quantify fracture‐matrix exchanges